Collaborative Governance in Creative Economy: A Case Study of the Tourism and Culture Department in Majalengka Regency - Ariesmansyah, Andre; Rosana, Mira (RMPI-BRIN, 2024)
The results of this study indicate that the Collaborative Governance Assessment process in the development of the creative economy at the Tourism and Culture Office of Majalengka Regency is progressing well. This success is attributed to the region's potential to develop creative industry facilities, particularly in the performing arts sector. The research concludes that the Collaborative Governance Assessment process in fostering the creative economy within the Department of Tourism and Culture of Majalengka Regency has been effective. Collaboration with various stakeholders, including creative economy actors and sponsors, has yielded positive outcomes and aligned with the expected targets. Furthermore, this collaboration has the potential to nurture young talents, paving the way for further advancement of the creative economy in Majalengka Regency.